2011
DOI: 10.1007/s00520-011-1279-5
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with fluoride custom trays in irradiated head and neck cancer patients

Abstract: Compliance with custom trays was poor in this series. Specific postirradiation dental care follow-up visits and education have demonstrated their utility in the era of 2D irradiation. We currently advocate an 18-month compliance with custom trays in IMRT patients on the basis of the Parsport trial, after which we assess the quality of salivary recovery before recommending prolonged use or interruption. Data with innovative irradiation techniques are however required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
4
36
2
1
Order By: Relevance
“…However, non-adherence rates are extremely high. As many as 81% of survivors do not adhere to oral care recommendations (Thariat et al 2012) and 87% do not adhere to swallowing exercise recommendations (Shinn et al 2013). This is problematic because poorly managed side effects are associated with treatment interruptions, social and emotional problems, and a more complicated and costly rehabilitation (Terrell et al 2004).…”
Section: Self-management Challenges After Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-adherence rates are extremely high. As many as 81% of survivors do not adhere to oral care recommendations (Thariat et al 2012) and 87% do not adhere to swallowing exercise recommendations (Shinn et al 2013). This is problematic because poorly managed side effects are associated with treatment interruptions, social and emotional problems, and a more complicated and costly rehabilitation (Terrell et al 2004).…”
Section: Self-management Challenges After Ocmentioning
confidence: 99%
“…As many as 81% of survivors do not adhere to oral care recommendations (Thariat et al . ) and 87% do not adhere to swallowing exercise recommendations (Shinn et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Daly et al [7] and Dreizen et al [8] reported the use of 1.0% neutral NaF, or NaF 2 gel (4,500 parts per million fluoride ion), applied daily in custom tray. However, the compliance with fluoride application in carriers by the population of patients with head and neck cancer is generally thought to be poor [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Nas publicações incluídas na revisão, foi mostrada a importância do uso do flúor e do Dental Maps para planejamento de tratamento odontológico pré e pós-radioterapia. 19,20 No E10 a adesão dos pacientes ao uso de moldeiras personalizadas foi pobre, 12 pacientes desenvolveram ORN e o estudo mostrou que o acompanhamento do paciente melhora essa adesão. O E11 mostrou que o Dental Maps seria uma importante ferramenta para o planejamento odontológico em pacientes pré e pós-radioterapia uma vez que ele é capaz de estimar a dose para cada dente e osso subjacente.…”
Section: Discussionunclassified